AKTIVITAS PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DASAR SEBAGAI ALTERNATIF PENGENALAN LINGKUNGAN SEKOLAH DI SEKOLAH DASAR - Andi Nurul Yusfiana; Ratnawati (Almeera Education, 2024)
Basic PLP is a compulsory course with a load of 2 credits, the main activity in the Basic PLP course is field practice by observing the school environment accompanied by reflective action under the guidance and supervision of the supervisor. The implementation of this PLP aims to build a foundation for the educator's identity and strengthen educational academic competence as well as form and improve student competence in aspects of attitude, knowledge and skills as prospective educators. The implementation of this PLP uses a qualitative descriptive method carried out with a block system that is traveled for 16 days, 4 days on campus and 12 days at school with an implementation time of 5 hours 40 minutes per day. Based on the results of direct observation, it shows that the discipline of school residents has been carried out well, the relationship between school residents is good. However, the relationship between students and students needs to be given direction so that students behave well with each other. With this introduction to the school field at SD Negeri 94 Balimbing, practitioners can find out the school profile, school management, school culture and culture, strengthening character education, as well as observing co-curricular, curricular activities and observing extracurricular activities.